Measuring equity of access to eye health outreach camps in rural Malawi. - Guillaume Trotignon; Thomas Engels; Shaneez Saeed Ali; Ziporah Mugwang'a; Iain Jones; Stevens Bechange; Effie Kaminyoghe; Tesfaye Haileselassie Adera; Elena Schmidt (PLoS ONE, 2022)
Introduction Equity in the access and use of health services is critical if countries are to make progress towards universal health coverage and address the systematic exclusion of the most vulnerable groups. The purpose of this study was to assess if the Co-ordinated Approach To Community Health programme implemented by Sightsavers was successful in reaching the poorest population, women, and people living with disabilities in Kasungu district, Malawi. Methods Between April and September 2017, data on socio-economic status, household characteristics and functional disability were collected from patients attending at eye camps in Kasungu district, Malawi. Using asset-based tools to measure household wealth (EquityTool© and Simple Poverty Scorecard©) and the Washington Group Short Set of Questions, individuals were categorised by wealth quintiles, poverty status, and functional disability status and then compared to relevant representative national household surveys. In addition, a follow-up household survey was conducted to check the validity of self-reported household characteristics at eye camps. Results A total of 1,358 individuals participated in the study. The study shows that self-reported data on household characteristics and assets are reliable and can be collected in clinical settings (instead of relying on direct observations of assets). Individuals attending outreach camps were poorer in terms of relative wealth and absolute poverty rates compared to the rest of the population in Kasungu. It was estimated that 9% of the participants belonged to the poorest quintile compared to 4% for the population in Kasungu (DHS 2015-2016). The ultra-poverty rate was also lower among respondents (13%) compared to 15% for Kasungu district (IHS 2017). The functional disability rate was 27.5% for study participants, and statistically higher than the general population (5.6%, SENTIF 2017). Even though women are more at risks than men, 54% of the participants were men. Conclusions Our study shows that existing tools can be reliably used, and combined, if based on recent population data, to assess equity of access to health services for vulnerable groups of the population. The findings suggest that the programme was successful in reaching the poorest people of the Kasungu district population as well as those with disabilities through outreach camps but that more men than women were reach through the programme. Subsequently, our study showed that self-reported household characteristics are a reliable method to measure asset-based wealth of camps' attendee. However, it is essential to use sub-national data (district or regional level) from recent surveys for the purpose of benchmarking in order to produce accurate results.